Exploration of microbial communities contributing to effective methane production from scum under anaerobic digestion. - Riku Sakurai (Public Library of Science (PLoS), 2021)
Scum is formed by the adsorption of long-chain fatty acids (LCFAs) onto biomass surface in anaerobic digestion of oily substrates. Since scum is a recalcitrant substrate to be digested, it is disposed via landfilling or incineration, which results in biomass washout and a decrease in methane yield. The microbes contributing to scum degradation are unclear. This study aimed to investigate the cardinal microorganisms in anaerobic scum digestion. We pre-incubated a sludge with scum to enrich scum-degrading microbes. Using this sludge, a 1.3-times higher methane conversion rate (73%) and a faster LCFA degradation compared with control sludge were attained. Then, we analyzed the cardinal scum-degrading microbes in this pre-incubated sludge by changing the initial scum-loading rates. Increased 16S rRNA copy numbers for the syntrophic fatty-acid degrader Syntrophomonas and hydrogenotrophic methanogens were observed in scum high-loaded samples. 16S rRNA amplicon sequencing indicated that Syntrophomonas was the most abundant genus in all the samples. The amino-acid degrader Aminobacterium and hydrolytic genera such as Defluviitoga and Sporanaerobacter became more dominant as the scum-loading rate increased. Moreover, phylogenic analysis on Syntrophomonas revealed that Syntrophomonas palmitatica, which is capable of degrading LCFAs, related species became more dominant as the scum-loading rate increased. These results indicate that a variety of microorganisms that degrade LCFAs, proteins, and sugars are involved in effective scum degradation.